Trophic ecology of rusty-spotted genet Genetta maculata and slender mongoose Herpestes sanguineus in Telperion Nature Reserve, with a focus on dietary segregation as a possible mechanism of coexistence - Zemouche, Julia (My University, 2018)
The diets of the rusty-spotted genet Genetta maculata and slender mongoose Herpestes sanguineus were investigated in Telperion Nature Reserve. A total of 196 genet scats and 97 mongoose scats were collected from latrines between April 2016 and August 2017. Scats were washed, oven dried at 50°C for 24 hours and their contents separated. Diet was determined through the identification of undigested food remains in the scats and hair scale patterns were used to identify which specific mammal species were consumed. Arthropod and small mammal abundance in Telperion Nature Reserve was also determined. Small mammals and arthropods were found to be the dominant prey of G. maculata, with birds, reptiles, seeds/fruit pulp, plant material and amphibians serving as supplementary food sources. Intermediate-to-high diet diversity and diet breadth indices were obtained for all seasons and diet overlap between pairs of seasons was also intermediate-to-high. For H. sanguineus, arthropods were the dominant prey, with mammals, birds, reptiles, seeds/fruit pulp, plant material and amphibians acting as supplementary food sources. Low-tointermediate diet diversity and low diet breadth indices were obtained for all seasons and diet overlap between pairs of seasons was very high. While no significant seasonal variation was observed for H. sanguineus, the seasonal peaks in availability of mammals and arthropods were found to coincide with peaks in the consumption of these two food categories by both species. The results therefore suggest that G. maculata is a generalist opportunist feeder and H. sanguineus is a generalist selector, with both species supplementing their diet when preferred food items become less abundant and varying diet according to season in response to seasonal changes in prey availability. Diet was fairly similar for these species, with dietary overlap being highest during spring and summer. Considering the dietary overlap observed, it is possible that trophic segregation on its own may not be enough to facilitate coexistence between G. maculata and H. sanguineus. However, the slight within-category differences that were noted may aid in decreasing trophic overlap. It is therefore possible that other factors such as temporal and spatial segregation, in conjunction with the slight trophic differences, aid in facilitating coexistence between G. maculata and H. sanguineus in Telperion Nature Reserve. Key words: arthropods, coexistence, diet, diet breadth, diet diversity, diet overlap, generalist feeder, generalist opportunist, generalist selector, Genetta maculata, Herpestes sanguineus, prey availability, scat analysis, small mammals, specialist feeder, trophic segregation.
A dissertation submitted in fulfilment of the requirements for the degree of Master of science (Zoology) in the School of Animal, Plant and Environmental Sciences at the University of the Witwatersrand 2018
Keywords: Animals--Food; Food chains (Ecology); Bioenergetics